Antidepressant Effects of NSAIDs in Rodent Models of Depression—A Systematic Review - Bay-Richter, Cecilie; Wegener, Gregers (Frontiers in Pharmacology, 2022)
In recent years much focus has been on neuroimmune mechanisms of depression. As a consequence, many preclinical and clinical trials have been performed examining potential antidepressant effects of several anti-inflammatory drugs. The results of such trials have been varied. With the current manuscript we wished to elucidate the effects of non-steroidal anti-inflammatory drugs (NSAIDs) on depressive-like behaviour in rodent models of depression by performing a systematic review of the available literature. We performed a systematic literature search in PubMed for rodent models of depression where NSAIDs were administered and a validated measure of depressive-like behaviour was applied. 858 studies were initially identified and screened using Covidence systematic review software. Of these 36 met the inclusion criteria and were included. The extracted articles contained data from both rat and mouse studies but primarily male animals were used. Several depression models were applied and 17 different NSAIDs were tested for antidepressant effects. Our results suggest that stress models are the best choice when examining antidepressant effects of NSAIDs. Furthermore, we found that rat models provide a more homogenous response than mouse models. Intriguingly, the use of female animals was only reported in 3 studies and these failed to find antidepressant effects of NSAIDs. This should be explored further. When comparing the different classes of NSAIDs, selective COX-2 inhibitors were shown to provide the most stable antidepressant effect compared to non-selective COX-inhibitors. Suggested mechanisms behind the antidepressant effects were attenuation of neuroinflammation, HPA-axis dysregulation and altered monoamine expression.